At the villa of reduced circumstances - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- Professor Dr. von Igelfeld entertainment novel., 2005)
Welcome to the insane and rarified world of Professor Dr. Moritz-Maria von Igelfeld of the Institute of Romance Philology. Von Igelfeld is engaged in a never-ending quest to win the respect he feels certain he is due<U+2013>a quest which has the tendency to go hilariously astray. In At the Villa of Reduced Circumstances, Professor Dr. von Igelfeld gets caught up in a nasty case of academic intrigue while on sabbatical at Cambridge. When he returns to Regensburg he is confronted with the thrilling news that someone from a foreign embassy has actually checked his masterwork, Portuguese Irregular Verbs, out of the Institute<U+2019>s Library. As a result, he gets caught up in intrigue of a different sort on a visit to Bogota, Colombia.